Microbial Communities and Interactions of Nitrogen Oxides With Methanogenesis in Diverse Peatlands of the Amazon Basin - Buessecker, Steffen; Zamora, Zacary; Sarno, Analissa F.; Finn, Damien Robert; Hoyt, Alison M.; van Haren, Joost; Urquiza Muñoz, Jose D.; Cadillo-Quiroz, Hinsby (Frontiers in Microbiology, 2021)
Tropical peatlands are hotspots of methane (CH4) production but present high variation and emission uncertainties in the Amazon region. This is because the controlling factors of methane production in tropical peats are not yet well documented. Although inhibitory effects of nitrogen oxides (NOx) on methanogenic activity are known from pure culture studies, the role of NOx in the methane cycling of peatlands remains unexplored. Here, we investigated the CH4 content, soil geochemistry and microbial communities along 1-m-soil profiles and assessed the effects of soil NOx and nitrous oxide (N2O) on methanogenic abundance and activity in three peatlands of the Pastaza-Marañón foreland basin. The peatlands were distinct in pH, DOC, NO3– pore water concentrations, C/N ratios of shallow soils, redox potential, and 13C enrichment in dissolved inorganic carbon and CH4 pools, which are primarily contingent on H2-dependent methanogenesis. Molecular 16S rRNA and mcrA gene data revealed diverse and novel methanogens varying across sites. Importantly, we also observed a strong stratification in abundances of microbial groups involved in NOx cycling, along with a concordant stratification of methanogens. The higher abundance of ammonia-oxidizing archaea (Thaumarchaeota) in acidic oligotrophic peat than ammonia-oxidizing bacteria (Nitrospira) is noteworthy as putative sources of NOx. Experiments testing the interaction of NOx species and methanogenesis found that the latter showed differential sensitivity to nitrite (up to 85% reduction) and N2O (complete inhibition), which would act as an unaccounted CH4 control in these ecosystems. Overall, we present evidence of diverse peatlands likely differently affected by inhibitory effects of nitrogen species on methanogens as another contributor to variable CH4 fluxes.